PREDIKSI KESULITAN KEUANGAN DENGAN ANALISIS Z-SCORE PADA PERUSAHAAN FOOD AND BEVERAGES - Satrio, Wahyu (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The researcher conducts the analysis of the financial report in the period of 2007 until 2011 at the food and beverages companies which is listed in The Indonesia Stock Exchange. The names of the companies arePT. Tiga Pilar Sejahtera Tbk, PT. Multi Bintang Indonesia Tbk, PT. Indofood Sukses Makmur Tbk, and PT. Sinar Mas Argo Tbk.The Analysis on this research is using the financial ratio analysis that is found on Z-Score model developed by Altman. Altmanâs Z-Score model is able to categorize the companies into three which are the companies with the financial difficulties, the companies with the susceptible financial difficulties and does not experience any financial difficulties.Keywords: Z-Score Analysis, The level of Financial Difficulties.